PERBANDINGAN NILAI DENSITAS CITRA MENGGUNAKAN GRID BERGERAK (MOVING GRID) POSISI HORISONTAL DAN VERTIKAL - Supriyati Supriyati; Wahyu Setia Budi; Heri Sutanto (Youngster Physics Journal, 2013)
In making radiographs  often differences exposure  factors used when using  moving  of horizontal and vertical. This study aims to determine the comparative value of the density of the resulting image when using a moving grid of horizontal and vertical position. So that research results can be applied in an effort to improve the quality of the radiograph. The study begins with the initial  test  without the grid to determine   density value, the second initial test using a moving grid both  horizontally  and vertically without  the  use  of material / objects.  Research   continued with three  aluminum thickness variation are  1 mm, 3 mm and 5 mm. Then using acrylic  material three thickness   variation are 1 cm,  2 cm and 3 cm. Results of image density measured using a densitometer.Results are then analyzed the data.  The  results  of research  show   value  of   the   image   using  horizontal    grid  density has    smaller  values  than    the  vertical    but   still within the   range  of  values density using   vertical   grid.  Thus   it can    be  said    that    the   image  density  values using  moving    grid   horizontal   position   is  not different with    density  of  the image using a vertical grid at the same exposure factors.Keywords: radiograph,  moving grid,  density,  comparison value